Flubendiamide, the first phthalic acid diamide insecticide, impairs neuronal calcium signalling in the honey bee's antennae. (August 2020) - Kadala, Aklesso; Charreton, Mercédès; Collet, Claude
Graphical abstract: Highlights: External and internal calcium are involved in detection of pheromones in honey bee. Insecticide flubendiamide disturbs intracellular calcium homeostasis. In vitro and calcium imaging assays are tools for insecticides risk assessment. Abstract: Calcium is an important intracellular second messenger involved in several processes such as the transduction of odour signals and neuronal excitability. Despite this critical role, relatively little information is available with respect to the impact of insecticides on the dynamics of intracellular calcium homeostasis in olfactory neurons. For the first time here, physiological stimuli (depolarizing current or pheromone) were shown to elicit calcium transients in peripheral neurons from the honey bee antenna. In addition, neurotoxic xenobiotics (the first synthetic phthalic diamide insecticide flubendiamide or botanical alkaloids ryanodine and caffeine) do interfere with normal calcium homeostasis. Our in vitro experiments show that these three xenobiotics can induce sustained abnormal calcium transients in antennal neurons. The present results provide a new insight into the toxicity of diamides, showing that flubendiamide drastically impairs calcium homeostasis in antennal neurons. We propose that a calcium imaging assay should provide an efficient tool dedicated to the modern assessment strategies of insecticides toxicity.